1990
DOI: 10.1099/00221287-136-1-69
|View full text |Cite
|
Sign up to set email alerts
|

RecA-independent high-frequency deletion of recombinant cosmid DNA in Escherichia coli

Abstract: Segments of DNA were deleted from recombinant cosmid DNAs during propagation in Escherichia coli hosts in liquid culture. DNAs of more than loo0 cosmids propagated in various E. coli hosts were analysed by agarose gel electrophoresis (AGE). The effects of vectors, insert DNAs and host genetic characters on the formation of deletions were examined. The probability of deletion and the pattern of deletion bands observed by AGE differed from clone to clone, and after extensive culture the deletion band patterns re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

1990
1990
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
8
1
Order By: Relevance
“…It is also possible that HIV-1 sequence contains some toxic sequence for bacterial replication although there has With regard to bacterial genetic machinery leading to HR, there are at least two independent systems, recA-dependent recBCD and recA-independent pathways. Ishiura et al [9,10] have previously reported the recA-independent deletion of the cosmid DNA and prevention of deletion in a recB recC sbcB recJ strains although the HR described there [10] involved short tandem repeats at the junction, which we did not observe in this study. Another recA-independent HR is reported by Symington et al [11] and Luisi-Deluca et al [12].…”
Section: Discussioncontrasting
confidence: 81%
“…It is also possible that HIV-1 sequence contains some toxic sequence for bacterial replication although there has With regard to bacterial genetic machinery leading to HR, there are at least two independent systems, recA-dependent recBCD and recA-independent pathways. Ishiura et al [9,10] have previously reported the recA-independent deletion of the cosmid DNA and prevention of deletion in a recB recC sbcB recJ strains although the HR described there [10] involved short tandem repeats at the junction, which we did not observe in this study. Another recA-independent HR is reported by Symington et al [11] and Luisi-Deluca et al [12].…”
Section: Discussioncontrasting
confidence: 81%
“…For example, B. aphidicola lacks recA, but recombination between its chromosomal DNA and plasmid DNA has been observed (Shigenobu et al, 2000;van Ham et al, 2003;Zientz et al, 2004). In addition, RecA-independent recombination has been reported in other bacteria such as Salmonella enterica and Campylobacter fetus (Albertini et al, 1982;Halliday and Glickman, 1991;Ishiura et al, 1990;Ray et al,2000;Schaaper and Dunn, 1991), although the mechanism is unknown. In phytoplasmas, it has been suggested that RecA does not function in either OY-M or AY-WB (Bai et al, 2006).…”
Section: Reca-independent Homologous Recombination In Phytoplasmamentioning
confidence: 95%
“…RecA independent recombination leading to deletions from recombinant plasmids has been described [15,18] but in these cases the plasmid was stable in both genetic backgrounds. It is clear that a recombination event giving rise to pHC7S occurs as soon as pHCF7 is introduced into S. typhimurium LT7 because all attempts to transform S. typhimurium LT7 with pHCF7 led to the recovery of pHC7S.…”
Section: Discussionmentioning
confidence: 99%
“…This plasmid was much smaller than the average size for the library. While it is quite common for cosmids which contain large inserts of foreign DNA to undergo deletions [15,16], the speed with which this small plasmid replaced the cosmids in the library is remarkable. We have demonstrated the presence of a cosmid (pHCF7) in the original library which contains a 40-kb insert of TML chromosomal DNA, and which possessed two regions of su¤cient similarity to allow homologous recombination.…”
Section: Discussionmentioning
confidence: 99%